Dance, modernity, and culture : explorations in the sociology of dance - Thomas, Helen, 1947- (Routledge, 1995)
Dance, modernity and culture explores an area of art practice that has long been marginalised by sociologists of art. As an important contribution to dance scholarship this book will be essential reading for anyone interested in the performing arts.